TAK1 in Vascular Signaling: “Friend or Foe”? - Fan G; Lu J; Zha J; Guo W; Zhang Y; Liu Y; Zhang L (Dove Medical Press, 2024)
Gang Fan,1,* Jingfen Lu,2,* Jinhui Zha,3,* Weiming Guo,1 Yifei Zhang,4 Yuxin Liu,5 Liyuan Zhang1 1Department of Urology, Huazhong University of Science and Technology Union Shenzhen Hospital, Shenzhen, 518052, People's Republic of China; 2The First Clinical Medical College of Guangzhou University of Chinese Medicine, Guangzhou, 510006, People's Republic of China; 3Shenzhen University, Shenzhen, 518000, People's Republic of China; 4The First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, Tianjin, 300193, People's Republic of China; 5College of Traditional Chinese Medicine, Hunan University of Chinese Medicine, Changsha, 410208, People's Republic of China*These authors contributed equally to this workCorrespondence: Liyuan Zhang; Gang Fan, Department of Urology, Huazhong University of Science and Technology Union Shenzhen Hospital, Shenzhen, 518000, People's Republic of China, Email liyuan.zhang@uszh.org.cn; gang.fan.med@qq.comAbstract: The maintenance of normal vascular function and homeostasis is largely dependent on the signaling mechanisms that occur within and between cells of the vasculature. TGF-β-activated kinase 1 (TAK1), a multifaceted signaling molecule, has been shown to play critical roles in various tissue types. Although the precise function of TAK1 in the vasculature remains largely unknown, emerging evidence suggests its potential involvement in both physiological and pathological processes. A comprehensive search strategy was employed to identify relevant studies, PubMed, Web of Science, and other relevant databases were systematically searched using keywords related to TAK1, TABs and MAP3K7.In this review, we discussed the role of TAK1 in vascular signaling, with a focus on its function, activation, and related signaling pathways. Specifically, we highlight the TA1-TABs complex is a key factor, regulating vascular smooth muscle cells (VSMCs) and endothelial cells (ECs) involved in the processes of inflammation, vascular proliferation and angiogenesis. This mini review aims to elucidate the evidence supporting TAK1 signaling in the vasculature, in order to better comprehend its beneficial and potential harmful effects upon TAK1 activation in vascular tissue.Keywords: TGF-β-activated kinase 1, vascular disease, mitogen-activated protein kinase, transforming growth factor-β, smooth muscle cell, endothelial cell